EKSTRACTION OF NICKEL LIMONIT USING DISSOLVED GASEOUS SO2-AIR - MARTHEN KINDA - NIM: 23016024, MEIYER
Nickel is a metal that is widely applied in the metal industry. The nickel ore is divided into two types, lateritic and sulphide. Indonesia is the third country to have the largest nickel reserves in the world. Indonesia's nickel ore reserves are dominated by laterite type. The laterite nickel is subdivided over two types of saprolite and limonite. Saprolite ore has a higher nickel content (1,8-3,0%) than limonite ore (0,8-1,5%). So the processing of saprolite nickel ore is more desirable than limonite nickel ore. One of the method used to process limonite nickel ore is extraction using SO2-air dissolved. The general objective of this research is to improve the nickel leaching process of limonite nickel by evaluating leaching method using SO2-air dissolved, and to modifing the initial treatment of ore using the alkali roasting. The variations used are acidity level of pH 1 and 3, alkali type for roasting (NaOH, Na2CO3, Na2SO4) and operating temperature at 55 and 80 oC. The extraction was carried out for 180 minutes and sampled at 15, 90, 120 and 180 minutes. The analysis was carried out by AAS method, mineralogy analysis using XRD, analysis, nickel result and selectivity. The results of the analysis stated that the pretreatment by alkali roasting can increase nickel recovery at the extraction stage. The addition of alkali Na2CO3, Na2SO4 and NaOH can extract nickel with the highest recovery at 23,99%; 28,15%; and 39.22%. The highest nickel recovery for pretreatment without alkali roasting is 14.80%. The optimum operating conditions for the highest extraction process are at pH 1 and temperature of 80oC. The highest nickel to iron selectivity was obtained for pretreatment without alkali addition at 24.946 at operating conditions pH 3 at 80oC and selectivity at 16.172 at operating conditions pH 3 at 55oC using adding Na2SO4.